Antaseden Kepuasan dan Loyalitas Penumpang Maskapai Penerbangan Low Cost Carrier di Indonesia - Raihanah Daulay; Roswita Hafni; Satria Mirsya Affandy Nasution (JURNAL ILMIAH MANAJEMEN & BISNIS, 2022)
Purpose - The purpose of this study was to formulate a model of passenger satisfaction and loyalty for Low Cost Carrier Airlines in IndonesiaMethodology - This type of research can be classified as causal research. This research was conducted in several big cities in Indonesia. Data collection was carried out by distributing questionnaires to respondents via the Google Form which was distributed using the WhatsApp application. In this study, the sample size was 250 passengers. The data analysis method used is Structural Equation Modeling (SEM) with LISREL 8.80 software.Findings - The results of the study show that Service Quality, Price, and Brand Image have a positive and significant effect on Trust. Service Quality, Price, and Brand Image have a positive and significant effect on Satisfaction. Service Quality, Price, Brand Image, trust and satisfaction have a positive and significant effect on Loyalty. Furthermore, there is the influence of Service Quality on Satisfaction through the Trust variable, there is the Effect of Price on Satisfaction through the Trust variable, there is the influence of Brand Image on Satisfaction through the Trust variable and there is the influence of Trust on Loyalty through the Satisfaction variable.Originality/Novelty - The research model uses five (5) variables and applies the concept of mediation, where each relationship in the research model is analyzed with SEM-Lisrel.Implications - This study has shown that trust and satisfaction have a mediating effect on the significant effect of Service Quality, Price, and Brand Image on loyalty. Starting from the results of this study, the recommendations for further research are to try to analyze or use the variables trust and satisfaction as independent variables, not as mediating variables.